Гендерна цифрова нерівність - Гасанова, Л. М. (ХНУРЕ, 2023)
Information technology is becoming increasingly part of our lives. At the same time, there is a gender imbalance in the possibility of access to modern information and communication technologies. The paper substantiates the idea that it is necessary to encourage and empower women so that they can play a more active role in the digital age. Women should have equal access to training at all levels, including programming and design, software development and information management. The inclusion and active participation of women is essential for a sustainable, fair and equitable economy and society.